The large-conductance calcium-activated potassium channel holds the key to the conundrum of familial hypokalemic periodic paralysis - June-Bum Kim; Sung-Jo Kim; Sun-Yang Kang; Jin Woong Yi; Seung-Min Kim (Korean Pediatric Society, 2014)
PurposeFamilial hypokalemic periodic paralysis (HOKPP) is an autosomal dominant channelopathy characterized by episodic attacks of muscle weakness and hypokalemia. Mutations in the calcium channel gene, CACNA1S, or the sodium channel gene, SCN4A, have been found to be responsible for HOKPP; however, the mechanism that causes hypokalemia remains to be determined. The aim of this study was to improve the understanding of this mechanism by investigating the expression of calcium-activated potassium (KCa) channel genes in HOKPP patients.MethodsWe measured the intracellular calcium concentration with fura-2-acetoxymethyl ester in skeletal muscle cells of HOKPP patients and healthy individuals. We examined the mRNA and protein expression of KCa channel genes (KCNMA1, KCNN1, KCNN2, KCNN3, and KCNN4) in both cell types.ResultsPatient cells exhibited higher cytosolic calcium levels than normal cells. Quantitative reverse transcription polymerase chain reaction analysis showed that the mRNA levels of the KCa channel genes did not significantly differ between patient and normal cells. However, western blot analysis showed that protein levels of the KCNMA1 gene, which encodes KCa1.1 channels (also called big potassium channels), were significantly lower in the membrane fraction and higher in the cytosolic fraction of patient cells than normal cells. When patient cells were exposed to 50 mM potassium buffer, which was used to induce depolarization, the altered subcellular distribution of BK channels remained unchanged.ConclusionThese findings suggest a novel mechanism for the development of hypokalemia and paralysis in HOKPP and demonstrate a connection between disease-associated mutations in calcium/sodium channels and pathogenic changes in nonmutant potassium channels.